Metabolic ecology : a scaling approach - Sibly, R. M.; Brown, James H., 1942 September 25-; Kodric-Brown, Astrid; Wiley InterScience (Online service) (Hoboken, NJ : Wiley-Blackwell, 2012)
"Most of ecology is about metabolism: the ways that organisms use energy and materials. The energy requirements of individuals - their metabolic rates - vary predictably with their body size and temperature. Ecological interactions are exchanges of energy and materials between organisms and their environments. So metabolic rate affects ecological processes at all levels: individuals, populations, communities and ecosystems. Each chapter focuses on a different process, level of organization, or kind of organism. It lays a conceptual foundation and presents empirical examples. Together, the chapters provide an integrated framework that holds the promise for a unified theory of ecology. The book is intended to be accessible to upper-level undergraduate, and graduate students, but also of interest to senior scientists. Its easy-to-read chapters and clear illustrations can be used in lecture and seminar courses. Together they make for an authoritative treatment that will inspire future generations to study metabolic ecology"--
"Explains the new metabolic theory of ecology, puts it into context, and shows how it can be used to answer contemporary problems"--
Front Matter -- Supplemental Images -- Introduction: Metabolism as the Basis for a Theoretical Unification of Ecology / James H Brown, Richard M Sibly, Astrid Kodric-Brown -- Foundations. Methodological Tools / Ethan P White, Xiao Xiao, Nick J B Isaac, Richard M Sibly -- The Metabolic Theory of Ecology and Its Central Equation / James H Brown, Richard M Sibly -- Stoichiometry / Michael Kaspari -- Modeling Metazoan Growth and Ontogeny / Andrew J Kerkhoff -- Life History / Richard M Sibly -- Behavior / April Hayward, James F Gillooly, Astrid Kodric-Brown -- Population and Community Ecology / Nick J B Isaac, Chris Carbone, Brian McGill -- Predatorb6(BPrey Relations and Food Webs / Owen L Petchey, Jennifer A Dunne -- Ecosystems / Kristina J Anderson-Teixeira, Peter M Vitousek -- Rates of Metabolism and Evolution / John L Gittleman, Patrick R Stephens -- Biodiversity and its Energetic and Thermal Controls / David Storch -- Selected Organisms and Topics. Microorganisms / Jordan G Okie -- Phytoplankton / Elena Litchman -- Land Plants: New Theoretical Directions and Empirical Prospects / Brian J Enquist, Lisa Patrick Bentley -- Marine Invertebrates / Mary I O'connor, John F Bruno -- Insect Metabolic Rates / James S Waters, Jon F Harrison -- Terrestrial Vertebrates / William Karasov -- Seabirds and Marine Mammals / Daniel P Costa, Scott A Shaffer -- Parasites / Ryan F Hechinger, Kevin D Lafferty, Armand M Kuris -- Human ecology / Marcus J Hamilton, Oskar Burger, Robert S Walker -- Practical Applications. Marine Ecology and Fisheries / Simon Jennings, Ken H Andersen, Julia L Blanchard -- Conservation Biology / Alison G Boyer, Walter Jetz -- Climate Change / Kristina J Anderson-Teixeira, Felisa A Smith, S K Morgan Ernest -- Beyond Biology / Melanie E Moses, Stephanie Forrest -- Synthesis and Prospect / James H Brown, Richard M Sibly, Astrid Kodric-Brown -- Glossary -- References -- Index.s
Includes index.
Machine generated contents note: Notes on contributorsPrefaceIntroduction: Metabolism as the basis for a theoretical unification of ecologyJames H. Brown, Richard M. Sibly, and Astrid Kodric-BrownPart I: Foundations1. Methodological toolsEthan P. White, Xiao Xiao, Nick J. B. Isaac, and Richard M. Sibly2. The metabolic theory of ecology and its central equationJames H. Brown and Richard M. Sibly3. StoichiometryMichael Kaspari4. Modeling metazoan growth and ontogenyAndrew J. Kerkhoff5. Life historyRichard M. Sibly6. BehaviorApril Hayward, James F. Gillooly, and Astrid Kodric-Brown7. Population and community ecologyNick J.B. Isaac, Chris Carbone, and Brian McGill8. Predator-prey relations and food websOwen L. Petchey and Jennifer A. Dunne9. EcosystemsKristina J. Anderson-Teixeira and Peter M. Vitousek10. Rates of metabolism and evolutionJohn L. Gittleman and Patrick R. Stephens11. Biodiversity and its energetic and thermalcontrols, 120David StorchPart II: Selected Organisms and Topics12. MicroorganismsJordan G. Okie13. PhytoplanktonElena Litchman14. Land plants: new theoretical directions and empirical prospectsBrian J. Enquist and Lisa Patrick Bentley15. Marine invertebratesMary I. O'Connor and John F. Bruno16. Insect metabolic ratesJames S. Waters and Jon F. Harrison17. Terrestrial vertebratesWilliam Karasov18. Seabirds and marine mammalsDaniel P. Costa and Scott A. Shaffer19. ParasitesRyan F. Hechinger, Kevin D. Lafferty, and Armand M. Kuris20. Human ecologyMarcus J. Hamilton, Oskar Burger, and Robert S. WalkerPart III: Practical Applications21. Marine ecology and fisheriesSimon Jennings, Ken H. Andersen, and Julia L. Blanchard22. Conservation biologyAlison G. Boyer and Walter Jetz23. Climate changeKristina J. Anderson-Teixeira, Felisa A. Smith, and S. K. Morgan Ernest24. Beyond biologyMelanie E. Moses and Stephanie Forrest25. Synthesis and prospectJames H. Brown, Richard M. Sibly, and Astrid Kodric-BrownGlossaryReferencesIndexUpdates and additional resources for this book are available from:http://www.wiley.com/go/sibly/metabolicecology.
Electronic reproduction.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Metabolism; Ecology; Biotic communities; SCIENCE -- Life Sciences -- Ecology; SCIENCE -- Life Sciences -- Biochemistry; Biotic communities; Ecology; Metabolism; Electronic books